Studi kelayakan pembangunan guest house (studi kasus: Guest House A) - Lyya Supriono; F. X Kristianta (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
The economic growth in the City of Madiun, which is showing good development, has led to an increase in Guest House entrepreneurs. One of these is the construction of Guest House A. This construction project can create opportunities for local workforce absorption and help boost the economy. This project needs to be reviewed to ensure that it is feasible, profitable, and sustainable in the long term, thus assisting investors in risk management and making informed decisions in running their business. To determine if the investment is considered feasible, an economic feasibility study needs to be conducted, considering several indicators such as Net Present Value (NPV), Net Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PBP). The first step is to conduct a literature study, then directly contact the parties involved in the construction to obtain accurate data, categorize revenue and costs, and observe the prevailing bank interest rates, followed by analysis using the established indicators. The calculations yielded an NPV of 1,053,103,006.39, an IRR of 12.88%, a BCR of 1.16, and a PBP of 10.93 years. The analysis results showed that the NPV is greater than zero, the IRR is higher than the MARR, and the BCR is greater than one, concluding that the investment can proceed. This study allows civil engineers to plan projects more thoroughly, considering financial aspects, market needs, and risks, thereby assisting in designing more realistic projects. Optimization of design and materials that consider cost and benefits can help in selecting effective solutions in terms of cost and sustainability.